ANXIETY AND METABOLIC DYSREGULATION: IMPLICATIONS OF THE HORMONAL AXIS IN GLYCEMIC CONTROL AND INSULIN RESISTANCE (CIPEEX, 2025)
Persistent anxiety and stress exert wide-ranging effects on both mental health and energy metabolism. Prolonged activation of the hypothalamic-pituitary-adrenal (HPA) axis leads to elevated cortisol secretion, disrupts circadian rhythms, and increases the release of inflammatory mediators. These physiological changes impair insulin sensitivity, elevate blood glucose levels, and promote visceral fat accumulation, thereby contributing to the development of insulin resistance. This review aims to present evidence on the interplay between anxiety, HPA axis function, and metabolic outcomes, drawing from original studies that assessed hormonal, inflammatory, and glycemic markers across diverse populations. Findings indicate that in adult workers, state anxiety is associated with higher evening cortisol and triglyceride levels, suggesting disruption of daily hormonal rhythms and an increased risk of cardiovascular alterations. Among women, perceived stress and burnout correlate with higher adiposity and hormonal imbalances, emphasizing the influence of emotional states on metabolic processes. In professionals exposed to high occupational demands, such as police officers, both psychological stress and oxidative stress contribute to the development of insulin resistance, highlighting multiple mechanisms of metabolic vulnerability.Overall, the evidence underscores that chronic anxiety and stress extend beyond emotional health, actively driving metabolic dysregulation. Recognizing this interaction deepens our understanding of the pathophysiology of insulin resistance and glycemic imbalance. Moreover, it emphasizes the importance of integrated strategies that promote mental well-being alongside metabolic health, aiming to prevent complications such as type 2 diabetes and cardiovascular disease.
Keywords: Anxiety; acne vulgar; estresse psicológico; inflamação cutânea; cortisol.; insulin resistance; Síndrome de Prader-Willi. Alterações metabólicas. Crianças